Effect of Respirator Resistance on Tolerant Capacity during Graded Load Exercise - 邱曼 王生 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
Respirator breathing resistance impacts performance of wearers during constant work load. However, it is less clear as to how breathing resistance affects the tolerant capacity of users during graded work load. The present study investigated the tolerant capacity of 8 individuals during incremental work load. The 8 subjects were required to wear two matched respirators （respirators Ⅰ and Ⅱ which were designed to have different breathing resistances and the same dead space） respectively on separate days and then work to end points. Minute ventilation （VE）, breathing frequency （BF）, oxygen consumption （VO2） and heart rate （HR） were recorded during exercise, while tolerant time, response time and breathing discomfort were measured at the end of each test trial. The test variables were com-pared between the two respirators by using matched-pairs t-test. The results showed that the tolerant time was significantly reduced for the respiratorⅠwith higher level of breathing resistance when compared with its counterpart with lower breathing resistance （respirator Ⅱ） （P〈0.05）. The same changes occurred for response time. Results also showed a significant increase in VE and BF for respirator Ⅰwearers when the work load was above 125 W. The O2 consumption was similar under the two breathing resistance conditions. These findings suggested that the respiratory resistance caused by self-contained breathing apparatus （SCBA） has an impact on the tolerant capacity of users.